Who benefits from free health insurance: Evidence from Mexico - Gabriella Conti; Rita Ginja (Institute for Fiscal Studies (IFS), 2023)
We present a comprehensive evaluation of the health impacts of the introduction and expansion of a large non-contributory health insurance program in Mexico, the Seguro Popular (SP). SP provided access to health services without co-pays to individuals with no Social Security protection. We identify the program impacts using its rollout across municipalities between 2002 and 2010. In general, we do not detect significant effects on mortality (overall or at any age); the only exception is a reduction in infant mortality (IM) in poor municipalities for which intention-to-treat estimates show a 10% decline due to SP. This decline is attributable to reductions in deaths associated with conditions originating in the perinatal period, congenital malformations, diarrhea and respiratory infections. In these poor municipalities, SP increased obstetric-related hospital admissions by 7%, and hospital admissions among infants by 6%. There were no impacts on mortality or use of hospitals in rich municipalities. The decline in IM rate caused by SP closed nearly all the IMR gap between poor and rich municipalities.
Keywords: H10; I12; I13; J13; O18; 330; Health Insurance; Infant Mortality; Health Care Utilization; Mexico